The Influence of Product Quality and Price on Purchasing Decisions: Brand Image as Mediation - Rahmawati, Christina Heti Tri; Solagracia, Stella (Universitas Bunda Mulia, 2024)
Consumer behavior is the activity of a person who participates directly in obtaining and using goods, including in making purchasing decisions and determining these activities. Purchasing decisions are the process of determining the choice to buy a product. Several factors that influence purchasing decisions include product quality, price, and brand image. The purpose of this research is to determine (1) the influence of product quality on purchasing decisions; (2) the influence of price on purchasing decisions; (3) the influence of product quality on purchasing decisions mediated by brand image; and (4) the influence of price on purchasing decisions mediated by brand image among consumers of Pantene Shampoo products in Yogyakarta. This research uses a population of all consumers of Pantene Shampoo products in Yogyakarta. This type of research is quantitative research using primary data in the form of questionnaires distributed to 96 respondents as research samples. This research uses data analysis techniques in the form of Structural Equation Modeling (SEM) with WarpPLS 6.0 software. The research results show (1) product quality has a positive effect on purchasing decisions; (2) price has no effect on purchasing decisions; (3) brand image partially mediates the influence of product quality on purchasing decisions; and (4) brand image does not mediate the influence of price on purchasing decisions among consumers of Pantene Shampoo products in Yogyakarta. The implications of the research results for companies can be used as a strategy to improve product quality and price, thereby forming a positive brand image and ultimately increasing purchasing decisions and company revenues.